A Single Nucleotide Mixture Enhances the Antitumor Activity of Molecular-Targeted Drugs Against Hepatocellular Carcinoma - Mao, Da; Xu, Meihong; Jiang, Qiyu; Sun, Huiwei; Sun, Fang; Yang, Ruichuang; Chai, Yantao; Li, Xiaojuan; Li, Boan; Li, Yong (Frontiers in Pharmacology, 2022)
New strategies for molecular-targeted drug therapy for advanced hepatocellular carcinoma (HCC) ignore the contribution of the nutritional status of patients and nutritional support to improve physical status and immunity. We aimed to elucidate the role of a single nucleotide mixture (SNM) in the anti-tumor therapy of HCC, and to explore the importance of a SNM as adjuvant therapy for HCC. Compared with a lipid emulsion (commonly used nutritional supplement for HCC patients), the SNM could not induce metabolic abnormalities in HCC cells (Warburg effect), and did not affect expression of metabolic abnormality-related factors in HCC cells. The SNM could also attenuate the lymphocyte injury induced by antitumor drugs in vitro and in vivo, and promote the recruitment and survival of lymphocytes in HCC tissues. Using HCC models in SCID (server combined immune-deficiency) mice or BalB/c mice, the SNM had anti-tumor activity, and could significantly upregulate the antitumor activity of molecular-targeted drugs (tyrosine-kinase inhibitors [TKI] and immune-checkpoint inhibitors [ICI]) against HCC. We employed research models in vivo and in vitro to reveal the anti-tumor activity of the SNM on HCC. Our findings expand understanding of the SNM and contribute to HCC (especially nutritional support) therapy.